5G-Enabled intelligent construction of a chest pain center with up-conversion lateral flow immunoassay. Issue 24 (23rd November 2021) - Huang, Lei; Tian, Shulin; Zhao, Wenhao; Liu, Ke; Ma, Xing; Guo, Jinhong; Yin, Ming
Abstract : Acute myocardial infarction (AMI) has become a worldwide health problem because of its rapid onset and high mortality. Abstract : Acute myocardial infarction (AMI) has become a worldwide health problem because of its rapid onset and high mortality. Cardiac troponin I (cTnI) is the gold standard for diagnosis of AMI, and its rapid and accurate detection is critical for early diagnosis and management of AMI. Using a lateral flow immunoassay with upconverting nanoparticles as fluorescent probes, we developed an up-conversion fluorescence reader capable of rapidly quantifying the cTnI concentration in serum based upon the fluorescence intensity of the test and control lines on the test strip. Reliable detection of cTnI in the range 0.1–50 ng mL −1 could be achieved in 15 min, with a lower detection limit of 0.1 ng mL −1 . The reader was also adapted for use on a 5th generation (5G) mobile network enabled intelligent chest pain center. Through Bluetooth wireless communication, the results achieved using the reader on an ambulance heading to a central hospital could be transmitted to a 5G smartphone and uploaded for real-time edge computing and cloud storage. An application in the 5G smartphone allows users to upload their medical information to establish dedicated electronic health records and doctors to monitor patients' health status and provide remote medical services. Combined with mobile internet and big data, the 5G-enabled intelligent chest pain center with up-conversion lateral flow immunoassay may predict the onset of AMI and save valuable time for patients suffering an AMI.